2020
DOI: 10.3390/ijms21186836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibroblast Growth Factor 21 on the Development of Atheromatous Plaque and Lipid Metabolic Profiles in an Atherosclerosis-Prone Mouse Model

Abstract: Fibroblast growth factor 21 (FGF21) is a hormonal regulator of lipid and glucose metabolism. We aimed to investigate the effect of an FGF21 analogue (LY2405319) on the development of atherosclerosis and its associated parameters. ApoE−/− mice were fed an atherogenic diet for 14 weeks and were randomly assigned to control (saline) or FGF21 (0.1 mg/kg) treatment group (n = 10/group) for 5 weeks. Plaque size in the aortic arch/valve areas and cardiovascular risk markers were evaluated in blood and tissues. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…In patients with type 2 diabetes (T2D), serum FGF15/19 levels are independently and inversely associated with arteriosclerosis parameters, supporting a protective role for serum FGF15/19 in atherosclerosis progression (W. S. Liu, Tang, et al, 2020). FGF21 also mitigates atherosclerosis in HFD‐fed ApoE −/− mice (Maeng et al, 2020). FGF21 also reduced Fas‐mediated apoptosis induced by oxidized LDL in HUVECs and in ApoE −/− mice (Yan et al, 2018).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…In patients with type 2 diabetes (T2D), serum FGF15/19 levels are independently and inversely associated with arteriosclerosis parameters, supporting a protective role for serum FGF15/19 in atherosclerosis progression (W. S. Liu, Tang, et al, 2020). FGF21 also mitigates atherosclerosis in HFD‐fed ApoE −/− mice (Maeng et al, 2020). FGF21 also reduced Fas‐mediated apoptosis induced by oxidized LDL in HUVECs and in ApoE −/− mice (Yan et al, 2018).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Shen et al showed that higher baseline serum FGF21 is associated with CVD mortality in elderly patients during the 5-year follow-up ( 12 ). In addition, the circulating level of FGF21 is also related to the development and prognosis of hypertension and atherosclerosis ( 13 ). Experimental studies show that FGF21 activating MAPK signaling through binding to FGFR1c and its co-receptorβ- Klotho to prevent myocardial hypertrophy ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the relationship between FGF21 and CVDs, such as CHD, [ 26 ] CMP, [ 27 ] and HF. [ 28 ] FGF21 exerts cardioprotective effects partly by regulating oxidative stress, [ 29 ] lipid metabolism, [ 30 ] autophagy, [ 31 ] and apoptosis [ 32 ] and may be a new target for the prediction and treatment of CVDs. In this study, we attempted to shed light on the recent progress in understanding the relationship between FGF21 and CVDs [Figure 1 ].…”
Section: Introductionmentioning
confidence: 99%